Wordwall Educational Games-Based Digital Assessment Development: An Innovative Approach to Indonesian Language Learning in Junior High Schools - Indriani, Puput; Zuhria, Azeta Fatha; Hidayat, Gilang Farid; Jaja, Jaja; Kurnia, Maya Dewi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a digital assessment model based on educational games using the Wordwall platform during Indonesian language learning activities at the junior high school level. This study employed the research and development method using the ADDIE model, which includes five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used included expert validation questionnaires and tests. Data analysis in this study was conducted using qualitative descriptive analysis. The findings revealed that the Wordwall-based digital assessment developed is proven to be valid and effective for application in Indonesian language learning, especially in advertising text, slogan, and poster material. This is evidenced by the results of validation by two experts and teachers, which showed that this assessment meets the aspects of content feasibility, practicality, and attractiveness with the categories of valid and highly valid. The gradual implementation of the Wordwall educational game-based digital assessment also showed a positive impact on student learning achievement, as observed from the increase in each student’s passing grade. Thus, the Wordwall educational game-based digital assessment can be an innovative learning tool that is fun, effective, and in line with 21st-century learning needs.